8s+9p=tp-9
adding -tp
8s+9p-tp=-9
8s+p(9-t)=-9
adding -8s
p(9-t)=-(8s+9)
p=-(8s+9)/(9-t)
=>(8s+9)/(t-9)
2007-01-14 04:26:32
·
answer #1
·
answered by raj 7
·
2⤊
0⤋
First: add 9 to both sides...
8s + 9p + 9 = tp - 9 + 9
8s + 9p + 9 = tp
*Subtract 9p from both sides...
8s + 9p - 9p + 9 = tp - 9p
8s + 9 = tp - 9p
Sec: factor the right side of the equation > find the least common factor which is, "p" ...
8s + 9 = p(t - 9)
Third: solve for "p" by isolating it on one side - divide both sides by "t - 9"
(8s + 9)/(t - 9) = [p(t - 9)]/(t - 9)
*Cancel "like" terms...
(8s + 9)/(t - 9) = p
p = (8s + 9)/(t - 9)
2007-01-14 12:28:10
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
Add 9 from both sides:
8s+9p+9=tp
Subtract -9p from both sides:
8s+9=tp-9p
Factor out a p:
8s+9=p(t-9)
Divide t-9 from both sides:
p=(8s+9)/(t-9)
2007-01-14 12:54:36
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
8s + 9p= tp - 9
8s + 9 = tp - 9p
8s + 9 = p(t - 9)
(8s + 9)/(t - 9) = p
2007-01-14 12:27:11
·
answer #4
·
answered by Tom :: Athier than Thou 6
·
2⤊
0⤋
math problem 8s+9p= tp-9 solve for p?
Answer: Take tp to the left hand side and 8s to the right:
9p-tp= - 8s-9 which we rewrite as:
p(9-t) = - (8s+9), which leads to :
p= - (8s+9)/(9-t)
2007-01-14 12:31:36
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
8s+9p= tp-9
8s + 9 = tp - 9p
8s + 9 = p (t - 9)
p = (8s + 9) / (t-9)
2007-01-14 12:27:04
·
answer #6
·
answered by car of boat 4
·
2⤊
0⤋
8s + 9p = tp - 9
tp - 9p = 8s + 9
p(t - 9) = 8s + 9
p = (8s + 9)/(t - 9)
2007-01-14 12:28:46
·
answer #7
·
answered by Helmut 7
·
2⤊
0⤋